Preparing the next generation for the Machine Age - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2017)
A book review of ‘Changing Jobs. The Fair Go in the Machine Age’ by Jim Chalmers and Mike Quigley, Redback 13, Schwarz Publishing, September 2017, 199 pp.